Women Entrepreneurship and Support Systems: A Literature Review - Adhikari, Puspa Raj (BIC Journal of Management, 2025)
This review elucidates the evolving paradigm of women's entrepreneurship worldwide, particularly in developing and emerging nations. Despite recent advancements, women entrepreneurs still encounter hurdles that significantly surpass those faced by their male counterparts. This study compiles modern studies in four important areas: the theoretical background of women's entrepreneurship, the special possibilities given to female entrepreneurs, and the infrastructure and support networks created to give them the higher success rate, and the challenges they continue to face. Through an extensive review of the literature, this synthesis brings forth issues common to a variety of geographical settings along with highlighting considerations unique to various regions. The findings indicate that, despite a conceptual recognition of the economic influence of women entrepreneurs, considerable deficiencies remain in the execution of targeted policies, access to funding, and sociocultural support. The review emphasizes that effective treatments must simultaneously address structural and cultural constraints. Further policy ideas encompass the creation of inclusive support networks tailored to the distinct requirements of women entrepreneurs, the promotion of gender sensitive policies, and the advocacy for further research into.